The Development of Happy Organization Indicators of Private Vocational Colleges in The Northeast: - Pradubsert, Rattavikran; Phoojomjit , Pongphop; Duangchatom, Kritkanok (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: The concept of a happiness organization is another idea aimed at promoting the quality of life in the workplace for individuals. It believes that fostering relationships within the organization leads to happiness. The feeling of being valued and having a sense of worth to the organization creates a sense of commitment, joy, love in work, and devotion to the organization. ready to dedicate physical and mental strength to contribute fullest potential of the organization. This research aims, to development of happy organization indicators and to test the goodness of fit of the structural relationship model of happy organization indicators of private vocational colleges in the Northeast with empirical data. Methodology: The research is divided into 2 phases. Phases 1 to development of happy organization indicators. The key informants group consisted of 9 experts, a sample group of 490 administrators and teachers. The research instrument is an interview form and a questionnaire. Statistics to analyze data by mean and standard deviation. Phase 2 to test the goodness of fit of the structural relationship model happy organization indicators of private vocational colleges in the Northeast with the empirical data, by second-order confirmatory factor analysis. Results: The indicators of the happy organization of private vocational colleges in the Northeast comprised 5 factors and 25 indicators, Happy people 5 indicators, Happy home 5 indicators, Organizational culture 5 indicators, Job satisfaction 5 indicators, and Happy Teamwork 5 indicators. 2. The goodness of fit of the structural relationship model of happy organization indicators of private vocational colleges in the Northeast. It was in good agreement with the empirical data, with Chi-Square = 3853.531, df = 270, P-Value = 0.000, CMIN/df. = 1.428, CFI = .962, GFI = 0.929 TLI = .958, AGFI= 0.915, RMSEA=0.033 RMR= 0.030, NFI= 0.886, IFI= 0.963. Every component had a statistically significant relationship at the 0.001 level. Conclusion: The consideration of workplace happiness is deemed a crucial factor in organizational management, particularly in the realm of human resource management. It has a significant impact on an individual level, fostering greater motivation and effectiveness in the workplace, and creating an atmosphere of happiness in the educational environment, administrators, teachers, and students collaboratively work together with full dedication and ability, resulting in improved operations and increased efficiency and effectiveness. Creating a positive image for the organization, and most importantly, the ultimate product of the educational institution: students who receive instruction from teachers working joyfully